Analisis Heterogenitas Spasial Tingkat Pengangguran Terbuka di Pulau Jawa Tahun 2024: Pendekatan Geographically Weighted Regression - Prayoga, Angga; Maulana, Alfarizi Rehan; Falson, Jauzie (Seminar Nasional Official Statistics, 2025)
Java Island is the center of the Indonesian economy with its largest contribution and high population density. However, unemployment remains a problem, and each region has different local characteristics. The indicator for measuring unemployment is the Open Unemployment Rate (TPT). Therefore, this study aims to determine the overview and factors influencing unemployment in districts/cities on Java Island, taking into account spatial heterogeneity in 2024. The data used are sourced from the Statistics Indonesia (BPS). The analytical method used is Geographically Weighted Regression (GWR). The results show that unemployment in each district/city is influenced by different factors. The TPAK and UMK have the greatest influence on the TPT in districts/cities on Java Island in 2024. The government needs to take a broader and more comprehensive approach to addressing unemployment, taking into account the specific conditions of each region.